Lost in time pulmonary metastases of renal cell carcinoma: complete surgical resection of metachronous metastases, 18 and 15 years after nephrectomy - Tsakiridis, Kosmas; Visouli, Aikaterini N.; Zarogoulidis, Paul; Mpakas, Andreas; Machairiotis, Nikolaos; Stylianaki, Aikaterini; Katsikogiannis, Nikolaos; Courcoutsakis, Nicolaos; Zarogoulidis, Konstantinos (Journal of Thoracic Disease; Vol 4, Supplement 1 (November 11, 2012): Journal of Thoracic Disease, 2012)
Surgery is the only potentially curative therapeutic approach for renal cell carcinoma (RCC). RCC is resistant to most systemic therapies, including chemotherapy, radiotherapy, and hormonal therapy, having limited response to immunotherapy. Newer agents targeting angiogenesis, recommended in metastatic RCC, offer improved disease free and overall survival, stabilizing the disease, rather than having a curative effect. One of the most common sites of synchronous or metachronous RCC metastases is the lung. The five-year survival after resection of RCC pulmonary metastases ranged between 21% and 83%. Complete metastasectomy improves the prognosis and should be evaluated, despite improved results of newer systemic treatments. In surgically treated metachronous RCC pulmonary metastases, the reported disease free interval varied, but in the majority of cases it did not exceed five years. Surgical resection of RCC pulmonary metastases 15 or more years after nephrectomy is very rare. We report complete surgical resection of metachronous, multiple, unilateral clear cell RCC pulmonary metastases in two patients without enlarged mediastinal lymph nodes or extrapulmonary disease, 15 and 18 years after initial nephrectomy. Both patients had an uneventful recovery, and remain alive and well one year, and five months respectively, after metastasectomy.